VD_FINDINFO HC / 2018 / 145 vom 24. Oktober 2017 - VD Tribunal cantonal (2017)
SERVITUDE DE CONDUITE, ACTION EN DOMMAGES-INTÉRÊTSEN GÉNÉRAL, EXPERTISE, FARDEAU DE LA PREUVE | 641 CC, 97 CO, 55 CPC (CH)